2022
DOI: 10.1128/mbio.02486-21
|View full text |Cite
|
Sign up to set email alerts
|

THOR’s Hammer: the Antibiotic Koreenceine Drives Gene Expression in a Model Microbial Community

Abstract: The diversity, ubiquity, and significance of microbial communities is clear. However, the predictable and reliable manipulation of microbiomes to impact human, environmental, and agricultural health remains a challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 69 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…However, the relative importance of these bacterial metabolites in their interactions with plants is yet to be explored. In addition, Flavobacterium has been selected as a member of the simplified model system involving three bacterial species coisolated from field-grown soybean roots to study community-level interactions [95,96]. Recent investigation showed that the dynamics and functions of this synthetic community may be modulated by and contribute to the regulation of secondary metabolism of the consortium members including Flavobacterium [97].…”
Section: Association With Host Health and Diseasementioning
confidence: 99%
“…However, the relative importance of these bacterial metabolites in their interactions with plants is yet to be explored. In addition, Flavobacterium has been selected as a member of the simplified model system involving three bacterial species coisolated from field-grown soybean roots to study community-level interactions [95,96]. Recent investigation showed that the dynamics and functions of this synthetic community may be modulated by and contribute to the regulation of secondary metabolism of the consortium members including Flavobacterium [97].…”
Section: Association With Host Health and Diseasementioning
confidence: 99%
“…Hurley et al probed the chemistry of THOR and revealed a major player in genetic regulation. Koreenceine, an antibiotic produced by P. koreensis , was found to be responsible for a large portion of differentially regulated genes in the other two community members . Without the initial detection of this compound and its BGC, significant factors in community survival and interaction would be overlooked.…”
Section: Microbiome Studiesmentioning
confidence: 99%
“…F. johnsoniae growth is inhibited by koreenceine, an antibiotic produced by P. koreensis , and koreenceine levels are modulated by the third THOR member, B. cereus (12). Gene expression and metabolite profiles of each member differ when they are in the community versus in pure culture (13, 14). These interactions indicate that THOR members engage in a web of biological interactions.…”
Section: Introductionmentioning
confidence: 99%